Participation of MyD88 and interleukin-33 as innate drivers of Th2 immunity to Trichinella spiralis. - FALLON, PADRAIC (My University, 2013)
Trichinella spiralis is a highly destructive parasitic nematode that invades and destroys intestinal epithelial cells, injures many different tissues during its migratory phase, and occupies and transforms myotubes during the final phase of its life cycle. We set out to investigate the role in immunity of innate receptors for potential pathogen- or danger-associated molecular patterns (PAMPs or DAMPs). Focusing on the MyD88-dependent receptors, which include Toll-like receptors (TLRs) and interleukin-1 (IL-1) family members, we found that MyD88-deficient mice expelled worms normally, while TLR2/4-deficient mice showed accelerated worm expulsion, suggesting that MyD88 was active in signaling pathways for more than one receptor during intestinal immunity. A direct role for PAMPs in TLR activation was not supported in a transactivation assay involving a panel of murine and human TLRs. Mice deficient in the IL-1 family receptor for the DAMP, IL-33 (called ST2), displayed reduced intestinal Th2 responses and impaired mast cell activation. IL-33 was constitutively expressed in intestinal epithelial cells, where it became concentrated in nuclei within 2 days of infection. Nuclear localization was an innate response to infection that occurred in intestinal regions where worms were actively migrating. Th2 responses were also compromised in the lymph nodes draining the skeletal muscles of ST2-deficient mice, and this correlated with increased larval burdens in muscle. Our results support a mechanism in which the immune system recognizes and responds to tissue injury in a way that promotes Th2 responses.
PUBLISHED
Keywords: Toll-like receptors; Immunology, Inflammation & Infection; Biomedical sciences